Foreign-born Teachers’ Experiences of Adaptation to Higher Education and Finnish Society - Tornberg, Anne; Alenius, Paulina; Korhonen, Vesa (Nordic Journal of Working Life Studies, 2025)
This article focuses on foreign-born teaching staff in higher education institutions and their experiences of cultural learning, as well as their psychological and sociocultural adaptation to their workplaces and to the Finnish society. Among highly skilled migrants, the area of foreign-born teaching staff in higher education is under-researched. This study is based on a qualitative thematic analysis of interviews of 13 foreign-born teachers. The findings showed that in the adaptation process, the place of living was particularly significant for the informants. Support from social and professional communities, as well as the informants’ own positive attitudes, fostered adaptation. Fluency in the local language promoted the informants’ social and professional adaptation and career development in higher education.